(Expression on numerator)k
= n+n^2+n^3+........+n^n)
= n(1+n+n^2+....+n^(n-1))
n^n-1
= n*--x------
n-1
Therefore, (expression on the numerator)/n^n
n 1
= -----* (1- ---- )k
n-1 n^n
n 1
Or, lim ----- * (1- ---- )
n-> infinity n-1 n^n
= 1*1
= 1
Lim (Expression on the denominator)/n^n
n-> infinity
1 2 (n-1)^n n^n
= lim ----- + ----+..........+ --------+ -------
n -> ∞ n^n n^n n^n n^n
= lim (1^n + (1-1/n)^n +(1-2/n)^n+.......)
n-> infinity
Now,
lim (1^n + (1-1/n)^n +(1-2/n)^n+.......)
n-> infinity
= 1+ 1/e + 1/e^2+.......
1 e
=----- = -------
1-1/e e-1
Consequently, required limit
= 1/(e/e-1)
= (e-1)/e
= 1- 1/e |